2021
DOI: 10.1111/jdv.17278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baricitinib in combination with topical steroids on atopic dermatitis symptoms, quality of life and functioning in adult patients with moderate‐to‐severe atopic dermatitis from the BREEZE‐AD7 Phase 3 randomized trial

Abstract: Background Baricitinib is an oral, selective, reversible Janus kinase 1/2 inhibitor approved in the European Union and Japan and under investigation in the United States for treatment of atopic dermatitis (AD). Objectives To evaluate the impact of baricitinib plus background topical corticosteroids (TCS) on health‐related quality of life (HRQoL), how AD symptoms impact work productivity and life functioning, and treatment benefit using patient‐reported outcome (PRO) assessments in patients with moderate‐to‐sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…This resulted in the approved dosage of 4 mg. A 2-mg dosage is recommended especially for age 75 and older, recurrent infections, or renal function impairment. In another phase III study focusing on quality of life and productivity, this also showed rapid and significant improvement as measured by various scores, including the Dermatology Life Quality Index (DLQI) and Patient Benefit Index (PBI) [ 42 ].…”
Section: Systemic Jak Inhibitorsmentioning
confidence: 99%
“…This resulted in the approved dosage of 4 mg. A 2-mg dosage is recommended especially for age 75 and older, recurrent infections, or renal function impairment. In another phase III study focusing on quality of life and productivity, this also showed rapid and significant improvement as measured by various scores, including the Dermatology Life Quality Index (DLQI) and Patient Benefit Index (PBI) [ 42 ].…”
Section: Systemic Jak Inhibitorsmentioning
confidence: 99%
“…With regard to other patient-reported outcomes, significantly (nominal p ≤ 0.01) more baricitinib 4 mg plus TCS than placebo plus TCS recipients achieved a clinically relevant ≥ 4-point improvement from baseline in the DLQI total score, a DLQI total score of 0 or 1 and a DLQI total score of ≤ 5 at week 16 [ 26 ]. Significant (nominal p ≤ 0.01 vs placebo plus TCS) between-group differences in these endpoints were seen at week 2 and all subsequent timepoints thereafter [ 26 ].…”
Section: Therapeutic Efficacy Of Baricitinibmentioning
confidence: 99%
“…With regard to other patient-reported outcomes, significantly (nominal p ≤ 0.01) more baricitinib 4 mg plus TCS than placebo plus TCS recipients achieved a clinically relevant ≥ 4-point improvement from baseline in the DLQI total score, a DLQI total score of 0 or 1 and a DLQI total score of ≤ 5 at week 16 [ 26 ]. Significant (nominal p ≤ 0.01 vs placebo plus TCS) between-group differences in these endpoints were seen at week 2 and all subsequent timepoints thereafter [ 26 ]. Baricitinib 4 mg plus TCS also provided a nominally significant improvement from baseline in itch (Table 2 ), and nominally significant changes from baseline in the POEM total score (Table 2 ) and the DLQI total score (nominal p < 0.001) compared with placebo plus TCS at week 16 [ 17 ].…”
Section: Therapeutic Efficacy Of Baricitinibmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding side effects, infections and increased blood CPK were the most common reported ones.A pulmonary thromboembolic event in a patient receiving baricitinib 4 mg was reported in BREEZE-AD7. The impact of the combined therapy in the health-related quality of life and productivity of AD patients, as well as the improvement in patient-reported outcomes were also assessed in BREEZE-AD7[22]. Both dosing regimens (2 mg and 4 mg) of baricitinib plus topical corticosteroids induced a rapidbefore week 2 -and significant improvement in several of the evaluated scores (Dermatology Life Quality Index, Work Productivity and Activity Impairment, Patient-Reported Outcomes Measurement Information System Itch and Sleep) when compared to placebo plus topical corticosteroids in the same timepoints.…”
mentioning
confidence: 99%